Pembentukan Karakter Dalam Perspektif Al-Qur’an - MUHAMMAD SOLEH RITONGA (Fitrah: Jurnal Kajian Ilmu-Ilmu Keislaman, 2020)
Character cannot just arise in a moslem, there are important things to do. The choice of figures is a very important thing to emulate. That figure is the prophet Muhammad, because the reflection of the Quran is all in the prophet Muhammad. He implements the Quran in his daily life. The problem occurred because the prophet Muhammad had left us, so imitating the character of the Prophet can no longer be directly, but it can be done indirectly by looking for information to Islamic scholars. But that is not enough, it needs the participation of muslims themselves in instilling a good character in him.